Uma plataforma de aquisição e processamento de imagens aéreas - Visentini, Gustavo César (2018)
The amplification of the field of vision of something of interest can bring several benefits, among them,the obtaining and analysis of data from cultivars in the agricultural environment in a more agile way.This is a process in which multiple images captured in sequence must be aligned according to points incommon between them, thus forming a mosaic or a large map. In this context, this work presents them development of an aerial image acquisition and processing platform, which integrates two softwares: an iOS application of autonomous Drones control, used to capture the images; and mosaic software usingthe OpenCV framework. As a case study, data from an experiment of Embrapa Trigo’s responsibility were used in experimental area II in Coxilha - RS. Using the platform and a TETRACAM multispectral sensor coupled to a Drone, NDVI data of the cultivars were collected and later an analysis explains that the NDVI obtained by the sensors presented a direct relationship with the cultivar productivity.